2021
DOI: 10.2166/wpt.2021.048
|View full text |Cite
|
Sign up to set email alerts
|

Multi-variate infilling of missing daily discharge data on the Niger basin

Abstract: The Niger basin have experienced historical drought episodes and floods in recent times. Reliable hydrological modelling has been hampered by missing values in daily river discharge data. We assessed the potential of using the Multivariate Imputation by Chained Equations (MICE) to estimate both continuous and discontinuous daily missing data across different spatial scales in the Niger basin. The study was conducted on 22 discharge stations that have missing data ranging from 2% to 70%. Four efficiency metrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Statistically significant trends and climate change signals were examined using the Student's t-test at a 95% confidence level 35 . The trend in the climate extreme events was calculated based on the Mann-Kendall trend test, while the trend's magnitude was estimated using Sen's slope 35,[44][45][46] .…”
Section: Climate Change Signals In Extreme Eventsmentioning
confidence: 99%
“…Statistically significant trends and climate change signals were examined using the Student's t-test at a 95% confidence level 35 . The trend in the climate extreme events was calculated based on the Mann-Kendall trend test, while the trend's magnitude was estimated using Sen's slope 35,[44][45][46] .…”
Section: Climate Change Signals In Extreme Eventsmentioning
confidence: 99%
“…Ekeu-wei et al [13] introduced the concept of multiple imputation to impute annual peak river discharge, which is vital for flood frequency estimation. Oyerinde et al [42] used the PMM method to impute missing data from 22 water discharge stations with different missing data percentages. However, these two studies failed to consider the missing data mechanism/pattern, which is important for handling missing data.…”
Section: Discussionmentioning
confidence: 99%
“…However, Madley-Dowd et al [70] found that, for data where values are missing according to the missing at random mechanism, imputation can provide unbiased results even with a large percentage of missing data (up to 90% missing). The study in [42] also considered missing data from 2% up to 70% of the dataset size for water discharge data. Therefore, it would be worth examining this further in the context of water level imputation, especially as even in one of the raw datasets (from the Makurdi water station) used to construct the multivariate data 68% of the water levels were missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the Mann-Kendall test [68][69][70] quantified the spatial trend, while the Student's t-test at a 95% confidence level [5,71] enumerated the significant plot.…”
Section: Utci Response To Lulc Categoriesmentioning
confidence: 99%